First characterization of three cyclophilin family proteins in the oyster, Crassostrea ariakensis Gould. (August 2016) - Xu, Ting; Xie, Jiasong; Yang, Shoubao; Ye, Shigen; Luo, Ming; Wu, Xinzhong
Abstract: Cyclophilins (CyPs) are a family of proteins that bind the immunosuppressive agent cyclosporin A (CsA) with high-affinity and belong to one of the three superfamilies of peptidyl-prolyl cis-trans isomerases (PPIase). In this report, three cyclophilin genes (Ca-CyPs), including Ca-CyPA, Ca-CyPB and Ca-PPIL3, were identified from oyster, Crassostrea ariakensis Gould in which Ca-CyPA encodes a protein with 165 amino acid sequences, Ca-CyPB encodes a protein with 217 amino acid sequences and Ca-PPIL3 encodes a protein with 162 amino acid sequences. All of the three Ca-CyPs genes contain a typical CyP-PPIase domain with its signature sequences and Ca-CyPB contains an N-signal peptide sequences. Tissue distribution study revealed that Ca-CyPs were ubiquitously expressed in all examined tissues and the highest levels were observed in hemocytes. RLO incubation upregulated the mRNA expression levels of Ca-CyPs, indicating that three Ca-CyPs might be involved in oyster immune response against RLO infection. Highlights: We firstly identified three cyclophilins (Ca-CyPs), including Ca-CyPA, Ca-CyPB and Ca-PPIL3 from the oyster, C. ariakensis . All the Ca-CyPs contain a typical CyP-PPIase domain with its signature sequences and Ca-CyPB contains an N-signal peptide. Tissue distribution studies revealed that Ca-CyPs were expressed in all examined tissues with the highest levels in hemocytes. RLO incubation increased the expression levels of Ca-CyPs, indicating Ca-CyPs might be involved in oyster immune response.